(untitled) (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2026)
Background and Aim. Physical activity is a key determinant of health-related quality of life (HRQoL), with well-established benefits for both physical and mental health. However, most studies have focused on overall physical activity, with limited attention to the distinct contributions of occupational and leisure-time activity. Furthermore, evidence on how these domains influence HRQoL across different age groups remains inconsistent. Therefore, this study aimed to examine the associations between occupational and leisure-time physical activity and HRQoL among working women aged 35–65 years. Methods. A cross-sectional study was conducted involving 107 working women aged 35–65 years, stratified into two groups (35–50 and 50–65 years). Physical activity was assessed using the Baecke Physical Activity Questionnaire (occupational, sports, and leisure-time domains). HRQoL was evaluated using the SF-36 Questionnaire. Statistical analysis was performed using SPSS, with independent samples t-tests used to assess group differences and Pearson correlation coefficients to examine associations between variables. Statistical significance was set at p < 0.05. Results. No significant differences in overall physical activity were found between age groups (p > 0.05). Women aged 35–50 years reported higher sport-related activity, whereas those aged 50–65 years engaged more in leisure-time activity. HRQoL scores declined significantly with age (p < 0.05), with the highest values observed in the younger group. In both groups, overall physical activity was positively associated with multiple HRQoL domains (p < 0.05). Stronger associations were observed between sport-related activity and HRQoL in the 35–50 group, and between leisure-time activity and HRQoL in the 50–65 group. Conclusions. Physical activity is positively associated with HRQoL among working women. Different activity domains may be more relevant at different ages, highlighting the importance of age-specific physical activity promotion strategies. Keywords: Physical activity; health-related quality of life; working women